2018
DOI: 10.3390/jfb9010004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Antimicrobial Activity of PLGA Films Loaded with 4-Hexylresorcinol

Abstract: Profound screening and evaluation methods for biocide-releasing polymer films are crucial for predicting applicability and therapeutic outcome of these drug delivery systems. For this purpose, we developed an agar overlay assay embedding biopolymer composite films in a seeded microbial lawn. By combining this approach with model-dependent analysis for agar diffusion, antimicrobial potency of the entrapped drug can be calculated in terms of minimum inhibitory concentrations (MICs). Thus, the topical antiseptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Systems that deliver their payloads at a predetermined rate and control the level of active ingredient within target tissues above the minimum effective level for prolonged periods help to reduce the dosing frequency (and concomitantly problems with patient compliance), which offer economic, environmental, health and societal impacts. There is a market need for delivery systems with sustained release of polar antimicrobials capable of eradicating bacterial growth in patients with weak immune systems [62,63,64,65,66,67,68]. Here we describe one method of loading high levels of antimicrobials in PLGA nanoparticles and demonstrate their efficacy against P. aeruginosa in vitro, using transient drug–polymer interactions for encapsulation and slow-release, and we envisage such systems to have potential for the treatment of respiratory infections [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems that deliver their payloads at a predetermined rate and control the level of active ingredient within target tissues above the minimum effective level for prolonged periods help to reduce the dosing frequency (and concomitantly problems with patient compliance), which offer economic, environmental, health and societal impacts. There is a market need for delivery systems with sustained release of polar antimicrobials capable of eradicating bacterial growth in patients with weak immune systems [62,63,64,65,66,67,68]. Here we describe one method of loading high levels of antimicrobials in PLGA nanoparticles and demonstrate their efficacy against P. aeruginosa in vitro, using transient drug–polymer interactions for encapsulation and slow-release, and we envisage such systems to have potential for the treatment of respiratory infections [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…There is a market need for the development of drug delivery systems and sustained release of polar antimicrobials capable of eradicating bacterial growth in patients with weak immune system [62,63,64,65,66,67,68]. Here we describe one method of loading high levels of antimicrobials in PLGA nanoparticles and demonstrate their efficacy against P. aeruginosa in vitro, using transient drug-polymer interactions for encapsulation and slow-release.…”
Section: Discussionmentioning
confidence: 99%
“…4-hexylresorcinol (4-HR) (Fig 1) is a synthetic derivative used as topical drug in antibacterial oral gargles and throat lozenges. [25] Recently, an incorporation of 4-HR within PLGA polymer composite films was proposed as a strategy to obtain biomedical and packaging products with antimicrobial properties. [25] In food industry, 4-HR is frequently used as a preservative and to prevent browning.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Recently, an incorporation of 4-HR within PLGA polymer composite films was proposed as a strategy to obtain biomedical and packaging products with antimicrobial properties. [25] In food industry, 4-HR is frequently used as a preservative and to prevent browning. [26] The widespread use in food industry and the antiseptic activity of 4-HR give rise to the assumption that 4-HR might be a safe adjuvant for antibiotic combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have found that hexylresorcinol has antibacterial activity against a range of species when in solution and when embedded in biopolymer composite films [18,19]. The antibacterial effects of hexylresorcinol in vivo may be mediated through several mechanisms including reducing bacterial adherence to the pharynx, inhibiting bacterial biofilm formation, disrupting bacterial cell chain formation, and modifying cell surface hydrophobicity [20].…”
Section: Introductionmentioning
confidence: 99%